The Determinants of the Rise of Sand Mining on the Batauga Coast of South Buton Regency - Hartini Amin (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This study aims to obtain information about the causes of the rise of sand mining on the coast of Batauga, South Buton Regency. This research uses a qualitative research design with a descriptive analysis method by describing it as it is about the reality obtained in the field. Data collection is done through observation and interview techniques. The results showed that the cause of the rise of sand mining in the Batauga District was caused by several factors, namely: 1). Low level of education and economic factors, sand mining activities do not require special expertise and can make money in a short time unlike farming or fishing, 2.) Lack of understanding and awareness, the community is relatively unaware of and aware of the long-term risks of mining sand, the conviction of the miners if the beach sand will never run out, and the belief that the coastal area is claimed the land as private property so that it has become the community's right to process it 3). Lack of socialization and no penalty (sanctions) for miners, 4). The existence of omission and granting of mining licenses from the government (legality) by withdrawing fees from sand mining.